2003
DOI: 10.1177/1091142102239135
|View full text |Cite
|
Sign up to set email alerts
|

On the Impact of Public Investment On the Performance of U.S. Industries

Abstract: omy and for 12 industries covering the whole spectrum of economic activity in the United States. Empirical results at the aggregate level indicate that public investment affects positively private inputs and private output. Empirical results at the industry level suggest that public investment tends to shift the sectoral composition of employment toward construction and transportation and the composition of private investment toward manufacturing, public utilities, and communications. Furthermore, public inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
39
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 15 publications
2
39
0
Order By: Relevance
“…Given the analysis of Pereira and Andraz (2013), who revealed a pattern of negative or not significant effects of infrastructure provision at the regional level and positive and significant effects at the aggregate level (Belloc and Vertova, 2006;Pereira and Andraz, 2005), we considered the case of spillover effects of the shinkansen on adjacent or neighboring regions. Earlier empirical evidence, for example, as gathered by Pereira and Andraz (2003) using a vector autoregression approach for transport and communication infrastructure, and Pereira and Roca-Sagales (2007) for highways, demonstrates positive spillover effects of infrastructure provision on neighboring regions. Table 1 gives two subsets of the spillover effects analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Given the analysis of Pereira and Andraz (2013), who revealed a pattern of negative or not significant effects of infrastructure provision at the regional level and positive and significant effects at the aggregate level (Belloc and Vertova, 2006;Pereira and Andraz, 2005), we considered the case of spillover effects of the shinkansen on adjacent or neighboring regions. Earlier empirical evidence, for example, as gathered by Pereira and Andraz (2003) using a vector autoregression approach for transport and communication infrastructure, and Pereira and Roca-Sagales (2007) for highways, demonstrates positive spillover effects of infrastructure provision on neighboring regions. Table 1 gives two subsets of the spillover effects analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Our results explain this hump-shaped structural change and provide a potential driving force for it. 3 Although previous work found that public expenditure was the driving force of structural change (Pereira and Andraz 2003;Dekle and Vandenbroucke 2012), their findings were quantitative, not theoretical. This paper develops a theoretical framework to study how public expenditure yields structural change along with constant growth rates of output.…”
mentioning
confidence: 86%
“…Whereas Ngai and Pissarides (2007) and Jensen and Larsen (2004) used different sectoral productivity growth rates to explain the movements 1 Some empirical works have found that public expenditure may be a source of structural change. For example, Pereira and Andraz (2003) used data involving 12 industries covering the US economy for and found that public investment positively affects employment. In particular, one million dollars invested in public capital creates about 27 jobs in the long term.…”
mentioning
confidence: 99%
“…Many papers address the uneven influence of public spending in various sectors. In this regard, Pereira and Andraz (2003) empirically test the importance of public spending on private-sector performance in the United States. The effect is heterogeneous across industries and the manufacturing sector is the biggest beneficiary.…”
Section: Preferences and Policy Variablesmentioning
confidence: 99%